2023
DOI: 10.1093/tas/txad045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sprouted whole pearl millet on growth performance, intestinal development, bacterial count, and blood indices of broiler chickens

Oluwakemi Olasehinde,
Foluke Aderemi

Abstract: This study investigated the effects of varying levels of sprouted whole grain pearl millet (SPM) on growth performance, intestinal morphology, microbial count, and blood indices of broiler chickens. A maize-soybean meal basal diet was formulated and fed to broiler chickens as starter (0 to 21 d) and finisher (22 to 42 d) diets. The diets comprised of 0, 25, 50, 75, and 100 % of SPM incorporated as whole grain. On 0 d, 180 unsexed broiler chickens were allocated to experimental diets in a completely randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Carcass traits and several internal organ parameters, as well as some blood parameters, improved in groups treated with additional germinated sprout feed (Fig. 2 and Tables 5, 6), which agrees with the ndings of Hassan (2020) and Olasehinde and Aderemi (2023), who demonstrated that the largest improvements in live body weight and body gain parameters were achieved with the barley grain or Pearl millet sprouting approach. Hassan (2020) demonstrated that the sprouting of barley grains increases the percentage of carcass at the same time for all barley levels while signi cantly slowing the accumulation of abdominal fat.…”
Section: Discussionsupporting
confidence: 86%
“…Carcass traits and several internal organ parameters, as well as some blood parameters, improved in groups treated with additional germinated sprout feed (Fig. 2 and Tables 5, 6), which agrees with the ndings of Hassan (2020) and Olasehinde and Aderemi (2023), who demonstrated that the largest improvements in live body weight and body gain parameters were achieved with the barley grain or Pearl millet sprouting approach. Hassan (2020) demonstrated that the sprouting of barley grains increases the percentage of carcass at the same time for all barley levels while signi cantly slowing the accumulation of abdominal fat.…”
Section: Discussionsupporting
confidence: 86%
“…The production performance of broilers was significantly improved when perilla seed meal replaces 1-2% soybean meal in the diet [22]. In addition, substituting soybean meal in the diet with plant protein raw materials like fermented rapeseed meal, raw chickpea, sweet almond meal, raw and fermented rapeseed cake, and sprouted whole pearl millet can also contribute to maintaining or even enhancing the growth and development of broilers [23][24][25][26][27]. In the experiment, the substitution of 5-10% soybean meal with ZBM significantly improved the ADG and ADFI of broilers, which supports the feasibility of using ZBM in broiler diets.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer's instructions, these biochemical parameters were analyzed by spectrophotometric (RAN-DOX, UK) using reagent kits (Randox, London, UK). Serum globulin was determined by subtracting the albumin concentration from total protein, as previously described by Olasehinde and Aderemi et al [35].…”
Section: Sample Collection and Analysis Of Blood Indicesmentioning
confidence: 99%